Blockchain Technology Applications in Education Sector: A Systematic Review and Scope for Further Research - Dr. Srinivasa Rao Bandaru, Dr. Sujatha Kamepalli, Dr. Chandrasekhara Rao Nannapaneni (International Journal of Advanced Science and Technology, 2020)
The potential of evidence-based sensible insights of a domain can ignite and illuminate research practice and scope for further research. Education sector is in the infancy stage in leveraging benefits of blockchain technology (BCT). This paper is an attempt to systematically review the applications of BCT in the education sector, to elicit the implicit/hidden scope for further research, to contribute to the expansion of the existing knowledge. The scientifically collected research articles, conference papers, and grey literature exclusively on BCT applications in the education sector are reviewed adopting the systematized review approach. The aim of the study is to explore and infer the existing BCT applications in the education sector highlight the potential implications and root level constraints for stakeholders; based on the review findings and evidence the scope for further research is highlighted.  The scope of the article is limited to the review of BCT applications, implications, and constraints to the education sector. This investigation will permit instructive foundations to evaluate and choose what BCT applications in education will be useful to them dependent on their individual organizational requirements. The review is not a fully systematic but systematized state-of-the-art review.  Some of the potential, feasible evidence-based educational areas seeking BCT applications are highlighted as scope for further research. The paper is an original systematized review in the domain.